2020
DOI: 10.1128/jvi.00058-20
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Zika Virus (ZIKV) Infection following Vaginal Inoculation with ZIKV-Infected Semen in Timed-Pregnant Olive Baboons

Abstract: Zika virus (ZIKV) infection is now firmly linked to congenital Zika syndrome (CZS), including fetal microcephaly. While Aedes species of mosquito are the primary vector for ZIKV, sexual transmission of ZIKV is a significant route of infection. ZIKV has been documented in human, mouse, and nonhuman primate (NHP) semen. It is critical to establish NHP models of the vertical transfer of ZIKV that recapitulate human pathogenesis. We hypothesized that vaginal deposition of ZIKV-infected baboon semen would lead to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
0
22
1
1
Order By: Relevance
“…Previous studies in nonpregnant NHP have shown that intravaginal ZIKV inoculation results in successful infection after a single challenge approximately 33-75 percent of the time ( 31 , 37 , 59 ). In pregnant olive baboons, a single intravaginal inoculation mid-gestation with semen containing ZIKV (originating from French Polynesia or Puerto Rico) resulted in 4 of 6 animals developing detectable vRNA in blood, with an additional animal having detectable vRNA in blood after a second inoculation ( 33 ). This was the rationale for the choice to perform repeat challenges at two-hour intervals in this study: in order to maximize the likelihood of establishing a productive infection in our small cohort within a single day.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in nonpregnant NHP have shown that intravaginal ZIKV inoculation results in successful infection after a single challenge approximately 33-75 percent of the time ( 31 , 37 , 59 ). In pregnant olive baboons, a single intravaginal inoculation mid-gestation with semen containing ZIKV (originating from French Polynesia or Puerto Rico) resulted in 4 of 6 animals developing detectable vRNA in blood, with an additional animal having detectable vRNA in blood after a second inoculation ( 33 ). This was the rationale for the choice to perform repeat challenges at two-hour intervals in this study: in order to maximize the likelihood of establishing a productive infection in our small cohort within a single day.…”
Section: Discussionmentioning
confidence: 99%
“…TBEV and ZIKV have been transmitted between laboratory mice by natural mating and SPONV RNA has been detected in the semen of infected mice [90,93,96,134]. Arboviruses detected in the reproductive tract and/or in sexual fluids of NHPs include CCHFV and ZIKV [24,[115][116][117][118][119][120][121][122][123]. Several arboviruses have also been detected in the reproductive tract or sexual fluids of livestock, including AKAV, BEFV, BTV, EHDV, JEV and SBV [37,42,132,143,156,157].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, ZIKV RNA was detected at high levels in the semen of male NHPs, remaining detectable for 28 days, with viral RNA also present but at lower levels in vaginal secretions of female NHPs [115]. ZIKV has been detected throughout the reproductive tracts of infected male and female NHPs [115,116,[118][119][120][121][122][123]. ZIKV RNA was detected in the testes and epididymis of male olive baboons for up to 10 and 41 days after infection [116].…”
Section: Zika Virus: Non-human Primate Models To Study Sexual Transmimentioning
confidence: 99%
“…Corroborating this, a prospective case study of a Brazilian woman demonstrated the presence of the antigen and viral genome in the vagina and endocervical samples up to the 31st day of Zika onset symptoms [ 13 ]. The high permissiveness of reproductive tract cells to ZIKV in-vitro infection has also been demonstrated [ 14 , 15 , 16 ]; studies in different experimental models have also pointed to the relevance of vaginal mucosa cells for ZIKV infection [ 17 , 18 , 19 , 20 ]. These data have demonstrated that infected semen in vaginal and endocervical mucosa can contribute strongly to the sexual transmission cycle and complications caused by ZIKV infection, such as male infertility and, especially, those associated with pregnant women [ 5 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%